1997
DOI: 10.1074/jbc.272.10.6471
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of NKT, a Gene Product Related to the Organic Cation Transporter Family That Is Almost Exclusively Expressed in the Kidney

Abstract: We have identified a gene product (NKT) encoding an apparently novel transcript that appears to be related to the organic ion transporter family and is expressed almost exclusively in the kidney. Analysis of the deduced 546-amino acid protein sequence indicates that NKT is a unique gene product which shares a similar transmembrane domain hydropathy profile as well as transporterspecific amino acid motifs with a variety of bacterial and mammalian nutrient transporters. Nevertheless, the overall homology of NKT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
200
1
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(212 citation statements)
references
References 31 publications
6
200
1
3
Order By: Relevance
“…14,[28][29][30][31] Similarly, homologous cDNAs that encode for a polyspecific renal anion transporter, OAT1 (also known as the paraaminohippurate transporter), have been recently identified, but also appear to be kidney-specific. [32][33][34] The rat and human OCT1 are kinetically similar to a renal proximal tubule and hepatocellular basolateral plasma membrane TEA transporter, and functionally characterized by NMN-inhibition of organic cation uptake. In fact, the NMN-inhibitable component of TEA uptake by Xenopus oocytes was the functional characteristic used to clone rOCT1.…”
Section: Discussionmentioning
confidence: 99%
“…14,[28][29][30][31] Similarly, homologous cDNAs that encode for a polyspecific renal anion transporter, OAT1 (also known as the paraaminohippurate transporter), have been recently identified, but also appear to be kidney-specific. [32][33][34] The rat and human OCT1 are kinetically similar to a renal proximal tubule and hepatocellular basolateral plasma membrane TEA transporter, and functionally characterized by NMN-inhibition of organic cation uptake. In fact, the NMN-inhibitable component of TEA uptake by Xenopus oocytes was the functional characteristic used to clone rOCT1.…”
Section: Discussionmentioning
confidence: 99%
“…This later proved to be true, but only in part, as several other transporters are now known to be involved. Soon after rOat1 had been cloned, other Oat1 orthologs were identified; in human, pig, rabbit, mouse, flounder and C. elegans [43][44][45][46][47][48][49][50][51]. To date, Oat1 message has been detected in kidney, choroid plexus and olfactory mucosa [52][53][54].…”
Section: The Organic Anion Transporter Familymentioning
confidence: 99%
“…Two members of this subfamily, SLC22A6 (also known as OAT1), originally identified as novel kidney transporter (NKT; Lopez-Nieto et al 1996, 1997 and SLC22A8 (also known as OAT3), originally identified as reduced in osterosclerosis (ROCT) (Brady et al 1999), function as the major basolateral transporters of a wide variety of drugs and toxins excreted via the proximal tubule of the kidney. These drugs include nonsteroidal anti-inflammatory drugs, antibiotics, antivirals (such as adefovir and cidofovir), antihypertensives, diuretics, methotrexate and many other commonly prescribed drugs (Eraly et al 2004a, b).…”
Section: Introductionmentioning
confidence: 99%